Spiritual intelligence: a scoping review on the gateway to mental health - Cristina Teixeira Pinto; Lúcia Guedes; Sara Pinto; Rui Nunes (Global Health Action)
Spiritual Intelligence (SI) is an independent concept from spirituality, a unifying and integrative intelligence that can be trained and developed, allowing people to make use of spirituality to enhance daily interaction and problem solving in a sort of spirituality into action. To comprehensively map and analyze current knowledge on SI and understand its impact on mental health and human interactions, we conducted a scoping review following the Joanna Briggs Institute methodology, searching for ‘spiritual intelligence’ across PubMedCentral, Scopus, WebOfScience, and PsycInfo. Quantitative studies using validated SI instruments and reproducible methodologies, published up to 1 January 2022, were included. Selected references were independently assessed by two reviewers, with any disagreements resolved by a third reviewer. Data were extracted using a data extraction tool previously developed and piloted. From this search, a total of 69 manuscripts from 67 studies were included. Most studies (n = 48) were conducted in educational (n = 29) and healthcare (n = 19) settings, with the Spiritual Intelligence Self Report Inventory (SISRI-24) emerging as the predominant instrument for assessing SI (n = 39). Analysis revealed several notable correlations with SI: resilience (n = 7), general, mental, and spiritual health (n = 6), emotional intelligence (n = 5), and favorable social behaviors and communication strategies (n = 5). Conversely, negative correlations were observed with burnout and stress (n = 5), as well as depression and anxiety (n = 5). These findings prompt a discussion regarding the integration of the SI concept into a revised definition of health by the World Health Organization and underscore the significance of SI training as a preventative health measure.